Taxmina NEUTRALIZATION OF MASCULINE IN ENGLISH: NEUTRALIZATION OF MASCULINE IN ENGLISH - Abduraximova, Taxmina (Журнал иностранных языков и лингвистики, 2022)
In the article we will try and show that our experience provides a starting point from which we conceptualize natural gender. It is this conceptualization, i.e. the fact that A can be seen as inherently linked with B, and not the actual masculine vs. feminine, of human vs. non-human, distinctions, that may account for some uses or gender as a linguistic category.